2005
DOI: 10.1182/blood.v106.11.679.679
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Histologic Grade on the Outcome of High-Dose Therapy and Autologous Stem Cell Transplantation for Follicular Lymphoma.

Abstract: Follicular lymphomas (FL) represent approximately one-fourth of all non-Hodgkins lymphomas (NHL) and are the most common indolent lymphomas. Studies suggest that patients (pts) with relapsed FL treated with high-dose therapy (HDT) and autologous stem cell transplantation (ASCT) have prolonged progression-free survival (PFS) and overall survival (OS) as compared to those treated with standard chemotherapy alone, yet the impact of histologic grade on these outcomes has not been established. In order to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A comparable benefit of high‐dose chemotherapy salvage and ASCT in relapsed G3 FL in the relapsed/refractory setting to low‐grade FL has been demonstrated in a retrospective review of 219 patients of which 17% were G3 FL. The PFS was similar among patients with G3 FL versus G1–2 FL 77 . An observational study by the Center for International Blood and Marrow Transplant Research evaluated the long‐term survival outcomes of 197 patients with relapsed G3 FL undergoing first reduced‐intensity conditioning allogeneic haematopoietic cell transplantation (allo‐HCT) or ASCT in the rituximab era.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparable benefit of high‐dose chemotherapy salvage and ASCT in relapsed G3 FL in the relapsed/refractory setting to low‐grade FL has been demonstrated in a retrospective review of 219 patients of which 17% were G3 FL. The PFS was similar among patients with G3 FL versus G1–2 FL 77 . An observational study by the Center for International Blood and Marrow Transplant Research evaluated the long‐term survival outcomes of 197 patients with relapsed G3 FL undergoing first reduced‐intensity conditioning allogeneic haematopoietic cell transplantation (allo‐HCT) or ASCT in the rituximab era.…”
Section: Treatmentmentioning
confidence: 99%
“…The PFS was similar among patients with G3 FL versus G1-2 FL. 77 An observational study by the Center for International Blood and Marrow Transplant Research evaluated the longterm survival outcomes of 197 patients with relapsed G3 FL undergoing first reduced-intensity conditioning allogeneic haematopoietic cell transplantation (allo-HCT) or ASCT in the rituximab era. The 5-year OS between groups was similar (59% vs. 54%, P = 0Á7).…”
Section: Relapsed Diseasementioning
confidence: 99%
“…As FL grading is dependent on precise recognition and counting centroblasts, inter‐ and intra‐observer reproducibility is challenging 13 . The clinical usefulness of grading FL has also been questioned 14–16 . Several studies have reported similar outcomes for patients of grades 1, 2, and 3A; in occasional studies, outcomes in patients with grade 3A are distinct from those with grades 1 & 2 17–19 .…”
Section: Introductionmentioning
confidence: 99%
“…13 The clinical usefulness of grading FL has also been questioned. [14][15][16] Several studies have reported similar outcomes for patients of grades 1, 2, and 3A; in occasional studies, outcomes in patients with grade 3A are distinct from those with grades 1 & 2. [17][18][19] Follicular lymphoma, grade 3B has been noted to be clinically and genetically distinct from the rest of FL.…”
mentioning
confidence: 99%